Mating competition and adult sex ratio in wild Trinidadian guppies. (14th June 2022) - Chuard, Pierre J C; Grant, James W A; Brown, Grant E
Abstract: Most experimental tests of mating systems theory have been conducted in the laboratory, using operational sex ratios (ratio of ready-to-mate male to ready-to-mate female) that are often not representative of natural conditions. Here, we first measured the range of adult sex ratio (proportion of adult males to adult females; ASR) in two populations of Trinidadian guppies ( Poecilia reticulata ) differing in ambient predation risk (high vs. low). We then explored, under semi-wild conditions, the effect of ASR (i.e., 0.17, 0.50, 0.83) on mating competition patterns in these populations. ASR in the wild was female-biased and did not significantly differ between the two populations. The range of ASR in our experiment was representative of natural ASRs. As expected, we observed an increase in intrasexual aggression rates in both sexes as the relative abundance of competitors increased. In support of the risky competition hypothesis, all measured behaviors had lower rates in a high versus low predation-risk population, likely due to the costs of predation. In terms of mating tactics, a male-biased ASR did not lead males to favor forced mating over courtship, indicating that males did not compensate for the cost of competition by switching to a less costly alternative mating tactic. Overall, this study highlights the need for field experiments using natural ranges of ASRs to test the validity of mating systems theory in a more complex, ecologically relevant context. Abstract : The proportion of sexually active adults that are males versus females (adult sex ratio) in a population shapes how individuals compete for mates. Most evidence for that theory comes from laboratory experiments. We replicated a mating competition laboratory experiment in the field using guppies. Our results show similarities and discrepancies between the laboratory and field experiments, and previous laboratory experiments only captured a portion of the natural range of adult sex ratios for that species.